Goldenberry flour as a natural antioxidant in Bologna-type mortadella during refrigerated storage and in vitro digestion. (February 2023) - Biasi, Vanessa; Huber, Eduardo; Goldoni, Thainá Sabrina Haefliger; de Melo, Ana Paula Zapelini; Hoff, Rodrigo Barcellos; Verruck, Silvani; Barreto, Pedro Luiz Manique
Abstract: Goldenberry is rich in phenolic compounds; however, no study has been carried out to assess its potential in meat products. The objective of the research was to characterize goldenberry ( Physalis peruviana ) fruits and flour and investigate its effect on the quality of Bologna-type mortadella, before and after in vitro digestion. Five treatments were performed: without antioxidant, with sodium erythorbate, and with three levels of goldenberry flour. The phenolic profile analysed by LC-MS/MS quantified 10 compounds in the fruit and 23 in the flour. Goldenberry flour did not affect the centesimal composition of the mortadella, but it had an effect on pH, hardness (texture profile) and color, as well as reduced lipid oxidation (peroxide value and TBARS) for 90 days. There was also an increase ( P < 0.05) in the antioxidant activity and in the content of phenolic compounds after in vitro digestion. Thus, goldenberry flour can be used as a natural antioxidant to replace sodium erythorbate in Bologna-type mortadella.